Perspectives on life participation by young adults with chronic kidney disease: an interview study. Issue 10 (16th October 2020) - Kerklaan, Jasmijn; Hannan, Elyssa; Hanson, Camilla; Guha, Chandana; Cho, Yeoungjee; Christian, Martin; Hamiwka, Lorraine; Ryan, Jessica; Sinha, Aditi; Wong, Germaine; Craig, Jonathan; Groothoff, Jaap; et al.
Abstract : Objective: To describe the perspectives on life participation by young adults with childhood-onset chronic kidney disease (CKD). Design: Semi-structured interviews; thematic analysis. Setting: Multiple centres across six countries (Australia, Canada, India, UK, USA and New Zealand). Participants: Thirty young adults aged 18 to 35 years diagnosed with CKD during childhood. Results: We identified six themes: struggling with daily restrictions (debilitating symptoms and side effects, giving up valued activities, impossible to attend school and work, trapped in a medicalised life, overprotected by adults and cautious to avoid health risks); lagging and falling behind (delayed independence, failing to keep up with peers and socially inept); defeated and hopeless (incapacitated by worry, an uncertain and bleak future, unworthy of relationships and low self-esteem and shame); reorienting plans and goals (focussing on the day-to-day, planning parenthood and forward and flexible planning); immersing oneself in normal activities (refusing to miss out, finding enjoyment, determined to do what peers do and being present at social events); and striving to reach potential and seizing opportunities (encouragement from others, motivated by the illness, establishing new career goals and grateful for opportunities). Conclusions: Young adults encounter lifestyle limitations and missed school and social opportunities as a consequence of developing CKD during childhood and as a consequence lack confidence and social skills, are uncertain of the future, and feel vulnerable. Some re-adjust their goals and become more determined to participate in 'normal' activities to avoid missing out. Strategies are needed to improve life participation in young adult 'graduates' of childhood CKD and thereby strengthen their mental and social well-being and enhance their overall health.